Decoding Employee Performance Through the Dynamics of Motivation, Stress, and Discipline - Busthomi, Yazidzil (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to analyze the influence of work motivation, job stress, and work discipline on employee performance at PT Aziz Jaya Abadi. Design/Methodology/Approach – This study employs a quantitative research approach. Data were collected from 92 employees of PT Aziz Jaya Abadi and analyzed using multiple linear regression to examine the relationship between the independent variables (work motivation, job stress, and work discipline) and the dependent variable (employee performance). Findings – The results indicate that work motivation, job stress, and work discipline have a positive and significant influence on employee performance. These findings suggest that improving these factors can enhance employee productivity and work efficiency at PT Aziz Jaya Abadi. Originality/Value This research provides value by empirically examining the combined influence of work motivation, job stress, and work discipline on employee performance within a single organizational context, offering practical insights to support performance improvement and operational efficiency.